Pengaruh Kegiatan Bermain Pasir Kinetik Terhadap Keterampilan Motorik Halus Anak Usia 4-5 Tahun: Studi Kuantitatif di RA Nurul Huda - Rahmawati, Wilujeng Rizki; Sumarni, Sri (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to determine the effect of playing with kinetic sand on the fine motor skills of children aged 4-5 years. Using a quantitative approach with a one-group pretest-posttest design, involving 10 children at RA Nurul Huda Lubuk Raja.Method – A quantitative research design was used, with test instruments as the main tool for data collection. This study used pre-test and post-test comparisons to assess the improvement of fine motor skills involving 10 children at RA Nurul Huda, complemented by paired T-test samples to measure the effectiveness of the intervention. Data analysis was conducted to determine whether the use of kinetic sand can make a significant contribution to children's fine motor skills. Findings – The results showed a significant improvement in children's fine motor skills. The pretest average value of 44% increased to 86.5% in the posttest, which showed an increase in student skills by 42.5%. The statistical test results using the t-test showed a significant increase, whereas the calculated t value of 3.54 was greater than the t-table value of 1.83. This finding confirms that kinetic sand acts as an effective sensory stimulation medium in improving children's fine motor skills. Research Implications – These findings provide empirical evidence that kinetic sand can be used as an effective instructional strategy to improve students' fine motor and thinking skills. This study supports the development of structured project-based educational practices to achieve more optimal cognitive outcomes.